2016
DOI: 10.58843/ornneo.v26i4.70
|View full text |Cite
|
Sign up to set email alerts
|

Genetics and Demography of Kelp Gulls in Patagonia

Abstract: The Kelp Gull (Larus dominicanus), a common seabird in coastal Patagonia, has recently increased in overall abundance and distribution, creating some concerns for the protection and conservation of other native, threatened species. We combined genetic and demographic data of four large Kelp Gull colonies distributed along 1800 km of the northern Patagonian coast of Argentina to further understand patterns of population growth and migration of the species. DNA analysis of variable intron sequences of two separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This is the first genetic study to include freshwater Kelp Gull colonies from Patagonia, and we find that those from Nahuel Huapi Lake are genetically differentiated from their closest coastal Atlantic and Pacific counterparts. Previous studies on Kelp Gulls have found genetic structure both at a South American continental scale [ 22 – 24 ] and among populations along the Argentine coast [ 16 ]. Particularly, Lyons et al [ 16 ] found some level of differentiation among the most geographically distant colonies in their study, as expected from a pattern of isolation by distance with gradually diminishing connectivity with distance along the Argentine coast.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is the first genetic study to include freshwater Kelp Gull colonies from Patagonia, and we find that those from Nahuel Huapi Lake are genetically differentiated from their closest coastal Atlantic and Pacific counterparts. Previous studies on Kelp Gulls have found genetic structure both at a South American continental scale [ 22 – 24 ] and among populations along the Argentine coast [ 16 ]. Particularly, Lyons et al [ 16 ] found some level of differentiation among the most geographically distant colonies in their study, as expected from a pattern of isolation by distance with gradually diminishing connectivity with distance along the Argentine coast.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on Kelp Gulls have found genetic structure both at a South American continental scale [ 22 – 24 ] and among populations along the Argentine coast [ 16 ]. Particularly, Lyons et al [ 16 ] found some level of differentiation among the most geographically distant colonies in their study, as expected from a pattern of isolation by distance with gradually diminishing connectivity with distance along the Argentine coast. Our findings also indicate closer affinities among colonies within each specific region, as opposed to the relationships observed between colonies situated in distinct geographic regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations